Witnessing as activism: Watching the other at the Israeli checkpoints. Issue 4 (1st October 2016) - Mansbach, Daniela
ABSTRACT: The practice of external witnessing—bearing witness to someone else's suffering—is often criticized as further destroying the victim's subjectivity. As a result, this approach limits the use of the practice to extreme cases in which victims lack the ability to speak for themselves. This article argues against limiting the use of the practice by tracing its potential to promote identification with the Other, thus undermining cases of dehumanization. This claim is developed through an analysis of the Checkpoint Watch movement in Israel, which reveals the way the movement challenges the dehumanization of the Palestinians. The activists address the delegitimation of the voice of the Palestinians through witnessing as representation and the unwillingness of the Israeli public to understand their experiences as suffering by witnessing as transformation. As such, this account calls for conceptualizing external witnessing as a prominent form of social and political activism.